2007
DOI: 10.1007/s00035-007-0786-y
|View full text |Cite
|
Sign up to set email alerts
|

Are the living collections of the world’s botanical gardens following species-richness patterns observed in natural ecosystems?

Abstract: Botanical gardens aim to promote the awareness, study and conservation of plant species diversity, but little is known about the species diversity of botanical gardens themselves. We therefore investigated whether the species richness of the worlds botanical gardens is related to their size, age and geographical location by compiling data from gardens in 124 different countries. The data show that even in these highly managed ecosystems, species richness can be described in terms of a relatively small number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 58 publications
0
25
1
2
Order By: Relevance
“…The purposes of botanical gardens include increasing public awareness and promoting research and the conservation of plant diversity (Wyse Jackson 1999;Pautasso and Parmentier 2007). Today there are more than 3,000 botanical gardens in 156 countries, with over 6 million accessions of living plants, and approximately 80,000 taxa in cultivation (Pautasso and Parmentier 2007;Dosmann and Groover 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purposes of botanical gardens include increasing public awareness and promoting research and the conservation of plant diversity (Wyse Jackson 1999;Pautasso and Parmentier 2007). Today there are more than 3,000 botanical gardens in 156 countries, with over 6 million accessions of living plants, and approximately 80,000 taxa in cultivation (Pautasso and Parmentier 2007;Dosmann and Groover 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Today there are more than 3,000 botanical gardens in 156 countries, with over 6 million accessions of living plants, and approximately 80,000 taxa in cultivation (Pautasso and Parmentier 2007;Dosmann and Groover 2012). One such garden is the Francisco Javier Clavijero Botanical Garden at the INECOL in Xalapa, Veracruz, Mexico, which is home to two living national collections: the national cycad collection and the Mexican national living bamboo collection.…”
Section: Discussionmentioning
confidence: 99%
“…However, their performance in urban vegetation has rarely been reported and is mostly focused on species-area curves. Most reported species-area curves demonstrate that species richness increase with expanding area size (Klotz, 1990;Pautasso and Parmentier, 2007), and the curves plotted for wooded patches in the urban context of Belgium fitted the semilog model very well (Godefroid and Koedam, 2003). However, in a study of different plant habitats and communities in the central city of West Berlin, the authors found that species richness increased with growing sampling size in a linear relationship, but showed no minimum sampling area trend (Sukopp and Werner, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses were performed in SAS 9.1. Spatial autocorrelation was controlled for using the procedure MIXED (as, e.g., in Pautasso and Parmentier 2007). Results from nonspatial (GLMs) and spatial models are qualitatively consistent, but (apart from the proportion of variance explained, which is obtained throughout from GLMs) we present only the more conservative analyses which take into account a potential spatial non-independence of data in terms of climate, survey intensity and species presence.…”
Section: Methodsmentioning
confidence: 99%